Management Indicators of Layur Fish (Trichiurus lepturus Linnaeus, 1758) in the Sunda Strait: Indikator Pengelolaan Ikan Layur (Trichiurus lepturus Linnaeus, 1758) di Selat Sunda - Rahmat Kurnia; Mennofatria Boer; Ikhlas Yati; Asep Agus Handaka Suryana (Journal of Tropical Fisheries Management, 2022)
Trichiurus lepturus has an important role at the tropic level and is an economically important fish. The purpose of this study was to examine management indicators in the form of time series of catches per effort (CPUE), asymptotic length over time, exploitation rate, ratio of first caught length (Lc) to first gonad maturity length (Lm), and spawning potential ratio (SPR). ). The research was conducted in the Sunda Strait, samples of fish landed at PPP Labuan, Banten. The analytical method used is long frequency analysis, surplus production model, and SPR analysis. The number of male and female fish observed was 396 and 299 respectively. The minimum length of male layur fish is 438 mm and 421 mm for females. The maximum length of the male layur is 843 mm and the female is 773 mm. CPUE results tend to increase from 0.416 in 2014 to 1.043 in 2019. The exploitation rate (E) of fish is 0.85 which indicates that it has experienced over exploitation. Asymptotic length 938.33 mm. The whitefish caught for the first time at Lc = 579.5 mm had an SPR of 13.10% and at Lm = 718.5 mm it had a fairly high SPR of 31.7%. Catch size occurs before layur fish spawn. SPR below the biological reference point. However, in 2019 there was an increase in catches allegedly due to a pause in fishing due to the tsunami in 2018.